Higher order thinking skills in teaching Malay language through questions and questioning among the teachers - Chew, F.P.; Hamad, Z.H.; Hutagalung, F. (2017)
This study was conducted to investigate the issues related to the level of knowledge acquisition in Higher Level Thinking Skills (HOTS) among the Malay language teachers in national primary schools. This study applied quantitative approach by using Bloom's Taxonomy (1956, 2001) and Intellectual Enhancement and Upbringing Model (Philips, 1996). Total of 60 teachers from one district in the Negeri Sembilan were selected to answer the HOTS test. In addition, this study also explored whether there were significant differences between the level of knowledge acquisition in HOTS questioning with teachers' social background. Data was analyzed by using SPSS version 21.0. The fmdings showed that the. level of knowledge acquisition of HOTS questioning in Malay language was at a moderate level. Mann-Whitney and Kruskall-Wal1is test showed no significant differences between the level of knowledge acquisition in HOTS questioning based on teachers' specialization, attendance to relevant courses and teaching experiences. In other words, the social background of teachers did not determined the level of knowledge acquisition in HOTS questioning technique among the Malay language teachers in national primary schools. Therefore, Ministry of Education need to conduct effective HOTS courses in order to ensure that the implementation of HOTS questioning technique in all schools a success.